(untitled) - Agresti, Alan (Hoboken, NJ, 2007)
An Introduction to Categorical Data Analysis, Second Edition is an invaluable tool for social, behavioral, and biomedical scientists, as well as researchers in public health, marketing, education, biological and agricultural sciences, and industrial quality control.
Keywords: Multivariate analysis,Phân tích đa biến